Manajemen Ekonomi Rumah Tangga Ala Maria Dalam Lukas 2:41-52 Dan Relevansinya Bagi Kaum Ibu Kristiani Masa Kini - Siprianus Soleman Senda; Rikardus Undat; Yohanes Subani; Theodorus Silab; Oktovianus M. Yuda Pramana; Polikarpus Mehang Praing (Jayapangus Press, 2026)
The story of the Holy Family in Luke 2:41-52 depicts a portrait of household economic management integrated with the values ​​of faith. This narrative depicts Mary not only as a mother who nurtured Jesus, but also as a figure who demonstrated wisdom, self-control, and responsibility in dealing with family dynamics. The background of this research departs from the reality of Christian mothers today who are faced with economic pressures, lifestyle changes, and moral demands in balancing domestic, work, and spiritual roles. The purpose of this research is to identify the principles of household economic management presented by Mary in Luke 2:41-52 and analyze their relevance for Christian mothers today. The method used is a study of biblical and theological literature linked to a socio-economic analysis of contemporary families. In addition, a comparative study of pastoral writings and spiritual reflections related to Mary's role was conducted to obtain a comprehensive picture of the practical values ​​contained in the narrative. The results of the study indicate that Mary's response to the crisis situation, especially the loss of Jesus in the Temple, demonstrates three main principles: emotional management rooted in faith, respectful communication within the family, and shared responsibility as the basis for decision-making. These findings identify that household financial management encompasses not only material aspects but also spiritual and relational dimensions that influence family well-being. This research confirms that the figure of Mary in this passage can serve as an inspiring paradigm for Christian mothers in building a household that balances economic needs and faith values, so that financial and parenting decisions are made wisely, patiently, and directed toward the family's spiritual growth.